(Chitosan-g-glycidyl methacrylate)-collagen II scaffold for cartilage regeneration. Issue 16 (1st November 2020) - Zarate-Triviño, Diana G.; Pool, Hector; Vergara-Castañeda, Hayde; Elizalde-Peña, Eduardo A.; Vallejo-Becerra, Vanessa; Villaseñor, Francisco; Prokhorov, Evgeny; Gough, Julie; Garcia-Gaitan, Beatriz; Luna-Barcenas, Gabriel
Abstract: Chitosan- g -glycidyl methacrylate (CTS- g -GMA)-collagen type II scaffold was synthesized and characterized as potential material for tissue engineering applications. Its physicochemical properties, biocompatibility and capacity to sustain chondrocytes proliferation were evaluated. FTIR, DSC and XRD analyses reveal that (CTSA- g -GMA)-collagen II copolymer ( Zcol ) possesses higher thermal stability and amorphous structure in contrast to the original polymers. Biocompatibility assays suggested that Zcol do not promote side effects in cell replication. Zcol allowed adhesion, growth, and proliferation of chondrocytes within 7 days. Our results suggest that (CTS- g -GMA)-collagen II copolymer may offer a new biomaterial alternative for cartilage regeneration. GRAPHICAL ABSTRACT: Synthesis of a (CTS-g-GMA)-collagen II scaffold for chondrocyte proliferation.